Description of a new species of the genus Zimiromus from Argentina (Araneae: Gnaphosidae) - Zapata, Lorena V.; Grismado, Cristian J. (Zootaxa, 2012)
The Neotropical genus Zimiromus Banks, 1914 was first revised by Platnick & Shadab (1976) and comprised at that time 21 species distributed from Mexico to Brazil. It was diagnosed by the combined presence of a strongly procurved posterior eye row (Figs. 5, 6), dentate tarsal claws, tarsi without false articulations, three promarginal cheliceral teeth, the male palp with a hook-like median apophysis, and the female epigynum usually with a scape (Platnick & Shadab 1976: 4). Subsequent contributions (Platnick & Shadab 1979, 1981, Platnick & Höfer 1990, Buckup & Brescovit 1993, Brescovit & Höfer 1994, Brescovit & Buckup 1998, Brescovit et al 2008) showed that the genus is more diverse; the current number of recognized species is 40 (Platnick 2012). This genus was traditionally assigned to the subfamily Echeminae (Platnick 1990) or, at least, considered related to the genus Echemus Simon (Murphy, 2007).